Perencanaan Pompa ESP Pada Sumur CNC-08 Untuk Meningkatkan Laju Alir Produksi - Lee, Michel; Lutfi, Mohammad; Afifah, Rohima Sera; Afrida, Afrida; Imbron, Muhammad; Rima, Maharani; Darmiyati, Iin (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Artificial Lift is a method used to enhance fluid pressure, enabling it to flow to the surface, particularly when the natural pressure of the well is insufficient. One type of Artificial Lift is the Electric Submersible Pump (ESP), which is inserted into the wellbore and operates using an electric motor to lift oil. This study aims to determine the optimal flow rate, the most suitable method for application, and the appropriate ESP pump design for the CNC-08 well. The well produces at a rate of 668.50 BPD, consisting of two liquid phases: oil and gas. The well data indicate that the bubble point pressure (Pb) exceeds the reservoir pressure; therefore, the two-phase Vogel method is applied to calculate the Inflow Performance Relationship (IPR). The ESP pump design results indicate an optimal flow rate of 774 BPD. The Vogel method is identified as the most appropriate approach. The recommended pump is the REDA AN900 type, with an efficiency of approximately 54%. The selected motor is a 540-series (30 HP, 435 volts, 45 A). The suitable cable type is 4 CU, while the transformer required is 2 x 25 KVA, and the switchboard type is DPH 2, size 72, type 3. Following the selection of appropriate components, a total voltage calculation was conducted. The results indicate a total voltage of 365.100 volts, which is lower than the available 435 volts. This confirms that the pump will operate effectively once installed. .